"Meat thermometer usage amongst European and North American consumers: A scoping review". (December 2019) - Elshahat, Sarah; Woodside, Jayne V.; McKinley, Michelle C.
Abstract: Improper cooking of meat contributes to many foodborne illnesses worldwide. The use of meat thermometers during cooking is recommended by food safety authorities in North America, but not yet in Europe. This scoping review investigated meat thermometer usage trends, consumers' barriers and facilitators, and usage-enhancing interventions, with the aim of informing potential policy changes as necessary towards enhancing meat thermometers usage. The study revealed that Europe is far behind North America in meat thermometer research and consumer use. The study results highlighted the increased compliance among mid-aged and higher socio-economic consumer groups. A considerable percentage of people do not use a meat thermometer, despite owning one and knowing its importance. Barriers to meat thermometer usage among consumers included: cooking habits, non-practicality, and the influence of society and media, whereas responsibility to dependents and enhancing meat quality were strong facilitators. Intervention studies showed that knowledge gain does not necessarily translate to behavior change, unless consumers' barriers and facilitators are addressed; hence behavioral theory-based interventions were most effective. The review concludes with recommendations for food safety authorities, starting with filling the research gap to understand consumers' attitudes and behaviors, followed by implementation and scaling-up of evidence-based interventions, associated with cost-effectiveness studies. Highlights: The study addressed consumers' attitudes and behaviours to meat thermometers usage. Meat thermometers usage trends in North America are higher than those in Europe. Several interventions in the US enhanced meat thermometers usage among consumers. We recommended several steps prior to policy changes in European cooking guidelines.